Social Learning Process in Household Electricity Theft: Case Study in Tanjung Burung Village, Teluknaga District, Tangerang Regency - Afiyah, Sayyidah Nailu (Devotion : Journal of Research and Community Service, 2023)
This study analyzes the collective theft of electricity in Tanjung Burung Village. This study uses descriptive qualitative research methods with data collection methods in the form of observation, interviews and documentation. The purpose of this study was to determine the processes and factors behind the collective occurrence of electricity theft. The theory used is social learning theory from Ronald Akers which focuses on four main concepts, namely differential association, definition, differential reinforcement, and imitation. In the theory put forward by Ronald Akers, there are values ​​of crime that are transmitted due to contact access that supports criminal behavior. The results of this study indicate that electricity theft in Tanjung Burung Village occurs due to differential associations where a person is confronted with profitable behavior to commit electricity theft so that electricity theft is considered a justifiable definition and not too bad to do. In addition, in electricity theft there is a differential amplifier in the form of rewards and punishments obtained. The punishments and rewards that are obtained by the perpetrators are generally not a deterrent because there are various ways to take peaceful paths so that the perpetrators can still be electrified illegally. The theft of electricity that continues to occur is motivated by the imitative behavior of previous perpetrators and is supported by weak laws or laws that don't work as they should, so that electricity theft is carried out collectively. This is done because the profits obtained are more dominant than the losses.